Acemannan accelerates cell proliferation and skin wound healing through AKT/mTOR signaling pathway. Issue 2 (August 2015) - Xing, Wei; Guo, Wei; Zou, Cun-Hua; Fu, Ting-Ting; Li, Xiang-Yun; Zhu, Ming; Qi, Jun-Hua; Song, Jiao; Dong, Chen-Hui; Li, Zhuang; Xiao, Yong; Yuan, Pei-Song; et al.
Highlights: Acemannan promotes skin wound healing and cell proliferation in vivo. Acemannan promotes cell proliferation by inducing cyclin D1 protein translation. Acemannan promotes cyclin D1 protein translation by Akt/mTOR signaling. Acemannan promotes fibroblasts proliferation by activation of Akt/mTOR signaling. Acemannan promotes skin wound healing by activation of mTOR signaling. Abstract: Background: Acemannan is a bioactive polysaccharides promoting tissue repair. However, the roles of acemannan in skin wound healing and the underlying molecular mechanisms are largely unclear. Objective: The goal of this study is to investigate the positive role of acemannan in cutaneous wound healing and its mechanism. Methods: Mouse skin wound model and skin primary fibroblasts were used to demonstrate the positive effect of acemannan on cutaneous wound healing. The expressions of cell proliferation nuclear antigen ki-67, cyclin D1 and activity of AKT/mTOR signaling were analyzed in acemannan-treated fibroblasts and mice. Rapamycin and AKT inhibitor VIII were used to determine the key role of AKT/mTOR signaling in acemannan-promoting cutaneous wound healing. Results: We found that acemannan significantly accelerated skin wound closure and cell proliferation. Acemannan promoted the expression of cyclin D1 in cultured fibroblasts, which was mediated by AKT/mTOR signal pathway leading to enhanced activity of the eukaryotic translation initiation factor-4F (eIF4F) and increased translation of cyclin D1. In contrast, pharmaceutical blockade of AKT/mTOR signaling by mTOR inhibitor rapamycin or AKT inhibitor VIII abolished acemannan-induced cyclin D1 translation and cell proliferation. In vivo studies confirmed that the activation of AKT/mTOR by acemannan played a key role in wound healing, which could be reversed by rapamycin. Conclusion: Acemannan promoted skin wound healing partly through activating AKT/mTOR-mediated protein translation mechanism, which may represent an alternative therapy approach for cutaneous wound.